3D printed Ti-5Cu alloy accelerates osteogenic differentiation of MC3T3-E1 cells by stimulating the M2 phenotype polarization of macrophages - Zhao, Xin; Zhou, Xing; Sun, Hui; Shi, Huixin; Song, Yiping; Wang, Qiang; Zhang, Guangping; Xu, Dake (Frontiers in Immunology, 2022)
Ti-5Cu alloy has been proved to have good mechanical properties and cell compatibility, and has certain antibacterial properties due to the addition of Cu. However, there are few studies on the effect of Ti-5Cu alloy on macrophage polarization and immune related bone formation. In this study, we prepared Ti-5Cu alloy by 3D printing technology, and found that Ti-5Cu alloy presented a much smoother surface compared with Ti. In addition, the CCK-8 results indicated that by co-culture method, Ti-5Cu alloy had no cytotoxicity to RAW264.7 cells. The results of ICP-MS showed that the concentration of Cu2+ was 0.133mg/L after 7 days of co-culture and the CCK-8 results proved that Cu2+ had no cytotoxicity to RAW264.7 at this concentration. Then, we studied the effects of Ti-5Cu alloy on macrophage polarization, results showed that Ti-5Cu was more prone to regulate the RAW264.7 polarization to M2 phenotype, the conditioned medium derived from Ti-5Cu alloy significantly promoted the proliferation and osteogenic differentiation of MC3T3-E1 cells. However, when the expression of OSM gene of RAW264.7 was knocked down, the osteogenic differentiation of MC3T3-E1 cells was decreased. This suggests that the OSM secreted by RAW264.7 co-cultured with Ti-5Cu alloy could accelerate the osteogenic differentiation of MC3T3-E1 cells.by acting on OSMR/gp130 receptors.